Silver(I) complexes with phthalazine and quinazoline as effective agents against pathogenic Pseudomonas aeruginosa strains - Glišić, Biljana; Senerovic, Lidija; Comba, Peter; Wadepohl, Hubert; Veselinovic, Aleksandar; Milivojevic, Dusan R.; Djuran, Miloš I.; Nikodinovic-Runic, Jasmina (Journal of inorganic biochemistry, 2016)
Five silver(I) complexes with aromatic nitrogen-containing heterocycles, phthalazine (phtz) and quinazoline (qz), were synthesized, characterized and analyzed by single-crystal X-ray diffraction analysis. Although different AgX salts reacted with phtz, only dinuclear silver(I) complexes of the general formula {[Ag(X-O)(phtz-N)]2(μ-phtz-N,N′)2} were formed, X=NO3− (1), CF3SO3− (2) and ClO4− (3). However, reactions of qz with an equimolar amount of AgCF3SO3 and AgBF4 resulted in the formation of polynuclear complexes, {[Ag(CF3SO3-O)(qz-N)]2}n (4) and {[Ag(qz-N)][BF4]}n (5). Complexes 1-5 were evaluated by in vitro antimicrobial studies against a panel of microbial strains that lead to many skin and soft tissue, respiratory, wound and nosocomial infections. The obtained results indicate that all tested silver(I) complexes have good antibacterial activity with MIC (minimum inhibitory concentration) values in the range from 2.9 to 48.0μM against the investigated strains. Among the investigated strains, these complexes were particularly efficient against pathogenic Pseudomonas aeruginosa (MIC=2.9-29μM) and had a marked ability to disrupt clinically relevant biofilms of strains with high inherent resistance to antibiotics. On the other hand, their activity against the fungus Candida albicans was moderate. In order to determine the therapeutic potential of silver(I) complexes 1-5, their antiproliferative effect on the human lung fibroblastic cell line MRC5, has been also evaluated. The binding of complexes 1-5 to the genomic DNA of P. aeruginosa was demonstrated by gel electrophoresis techniques and well supported by molecular docking into the DNA minor groove. All investigated complexes showed an improved cytotoxicity profile in comparison to the clinically used AgNO3.